Vpliv aerobne vadbe na obvladovanje simptomov pri ankilozirajočem spondilitisu - Maučec, Saša (Šport (Ljubljana), 2023)
Ankylosing spondylitis (AS) is one of the most common inflammatory rheumatic diseases. It mostly affects younger adults, which includes most professional and recreational athletes. The beneficial effects of exercise training in AS have been known for many years, but there are few studies examining the effect of aerobic training on AS symptoms. The aim of our systematic review was to determine the effectiveness of aerobic exercise training on symptom management in individuals with AS. We searched the literature on the PubMed, Medline, CINAHL and Cochrane Library databases, combining the following keywords: ankylosing spondylitis, aerobic training, exercise and activity. We included randomised controlled trials, with at least one experimental group receiving aerobic exercise, regardless of the type, duration and intensity of exercise, and a control group receiving different type of treatment or no intervention. Based on the inclusion and exclusion criteria, six studies were finally included in this review. Aerobic exercise was associated with a beneficial effect on reducing disease activity, improving spinal mobility and reducing pain. However, due to a high heterogeneity and few high-quality studies, definite conclusions regarding athletes with AS could not be drawn. To establish clear clinical guidelines, we need high quality studies, with a larger sample of subjects, investigating the long-term effects of aerobic exercise.
Keywords: aerobna vadba; aerobni trening; ankilozirajoči spondiltis; kronični revmatizem; raziskave; šport